Digitalisasi Terkait Penyebaran Judi Online & Pinjaman Online Dalam Perspektif Pendidikan Islam - Novianti, Dian; Nur Ibrahim, Rohmat; Fathur Rohman SW, Oman (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
The rapid development of digital technology has transformed patterns of human behavior, including the proliferation of online gambling and digital lending platforms. While digitalization offers convenience and accessibility, it has simultaneously generated new social and moral challenges, particularly among students and young adults. This study examines the impact of online gambling and online loans from the perspective of Islamic education, focusing on moral degradation, financial vulnerability, psychological risks, and the erosion of religious values. Using a qualitative-descriptive approach supported by contemporary literature (2020–2025), this paper analyzes how digital platforms contribute to addictive behavior, instant gratification tendencies, and weakening of self-control (mujahadah al-nafs). The findings show that exposure to online gambling and unregulated digital lending leads to high-risk financial decisions, academic decline, stress, and detachment from ethical Islamic principles such as amanah, qana’ah, and maslahah. Islamic education plays a crucial role in mitigating these risks through value-based digital literacy, strengthening character education, and guiding students to navigate the digital world responsibly. This study concludes that a holistic Islamic educational approach—integrating moral-spiritual reinforcement, technological awareness, and family-school-community collaboration—is essential to counter the negative impacts of digitalization in the modern era.